Upaya Peningkatan Hasil Belajar Ilmu Pengetahuan Sosial Materi Pengaruh Interaksi Sosial Terhadap Kehidupan Sosial dan Kebangsaan Melalui Model Jigsaw - Susanto, Agus (Universitas Nusantara PGRI Kediri, 2022)
This study uses the Jigsaw Cooperative Learning Model with social interaction competency standards on social life and nationality in class VIII students. The basis for describing the influence of social interaction on social life and nationality through the Jigsaw Model. The purpose of this study was to objectively determine the increase in social studies learning outcomes through the Jigsaw Model in the matter of increasing social science learning outcomes in material about the influence of social interaction on social and national life through the Jigsaw Model for Class VIII-B Students Semester 1 of the 2022/2023 Academic Year in SMP Negeri 1 Pogalan. This research method is Action Research with the Stephen Kemmis model. This Jigsaw learning model is designed in two cycles. Research results In the first cycle of student learning outcomes have not reached completeness. The average value is 65.625. There are 18 students who achieve completeness with a percentage of 55.00%. In cycle II, student learning outcomes have reached completeness. The average value is 79.37. There were 19 students who achieved completeness with a percentage of 93.75%. The conclusion of this study, the Jigsaw Technique can improve social studies learning outcomes in material The influence of social interaction on social life and nationality through the Jigsaw Model in Class VIII-B Semester 1 Academic Year 2022/2023 at SMP Negeri 1 Pogalan. Based on this conclusion, it is suggested that teachers always improve learning outcomes by choosing methods or media that are appropriate to the characteristics of teaching materials and students.